The Relationship of Two Traits: Explosive Strength and Distinctive Strength with Leg Speed to the Accuracy of High-Smashing Performance by Dhi Qar University Volleyball Team Players - Kadhim, Amjad Abd (University of Thi-Qar Journal, 2025)
The goals of the research search out recognize the principles of explosive capacity with the performers of the University of Dhi-Qar volleyball group, and to recognize the principles of the capacity characteristic of speed with the performers of the University of Dhi-Qar volleyball group and Identify the friendship betwixt the explosive force and the capacity characteristic of speed and veracity of the efficiency of the ability of the overpowering extreme front with the performers of the University of Dhi Qar volleyball crew, and the scientist secondhand the explanatory approach in the design of correlational connections, and the scientist selected the research sample from the performers of the University of Dhi-Qar crew, whose number attained (8) in another direction (14), and accordingly the portion of the research sample is (57.14%), and individual of ultimate main decisions The life of a meaningful equivalence between explosive strength and distinctive strength with leg speed to the accuracy of high-smashing performance by Dhi Qar University volleyball team players